Monuments and contemporary sculptural art in Iraq from 1921 to 1990 - Shirwan Ali Hamaxan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Monumental art starts with English colonial rule in Iraq. Monumental art occupies a more prominent swath of public space when the nationalist groups took over power from the 1960s and 1970s. In the two subsequent decades, Iraq dedicated the largest subsidies to creation of public monuments on a global level. These monuments represented public values that emanated from their relations to state institutions. More than any other art medium, monuments are entangled with problematics in Iraq. However, monuments within the literature of art criticism have received the least attention. The objective of this research is to shed light on the hidden narrative behind the production of monuments in contemporary sculpture practices. This aims at opening dialogue on the main perspectives of the intellectual and political elite on cultural identity in Iraq